2016
DOI: 10.4269/ajtmh.15-0892
|View full text |Cite
|
Sign up to set email alerts
|

Spatial–Temporal Co-Circulation of Dengue Virus 1, 2, 3, and 4 Associated with Coinfection Cases in a Hyperendemic Area of Brazil: A 4-Week Survey

Abstract: Abstract. Dengue is currently regarded as a major public health problem worldwide. In a hyperendemic region during an outbreak, we detected the co-circulation of all Dengue virus (DENV) serotypes including two different genotypes of DENV-3 and DENV-4, and concurrent infections with up to three serotypes were identified in symptomatic patients. A total of 49 acute phase plasma samples from patients clinically suspected of dengue were collected during the 4 weeks of May 2013. DENV-1-4 was detected by reverse tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 14 publications
1
18
0
2
Order By: Relevance
“…Also, we report for the first time genomic-based evidence of dengue virus co-infection with DENV-1 and DENV-3 serotypes during a single phase of outbreak in Tanzania. Dengue concurrent infections have been commonly reported in endemic countries including Brazil [29] and India [30]. Dengue concurrent infections have serious clinical implication for patient management, as they can present with severe clinical manifestations such as haemorrhagic fever syndrome [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Also, we report for the first time genomic-based evidence of dengue virus co-infection with DENV-1 and DENV-3 serotypes during a single phase of outbreak in Tanzania. Dengue concurrent infections have been commonly reported in endemic countries including Brazil [29] and India [30]. Dengue concurrent infections have serious clinical implication for patient management, as they can present with severe clinical manifestations such as haemorrhagic fever syndrome [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…One lineage was estimated to be introduced into Divinópolis around 2007, and the second was estimated to be introduced into the city around 2011 and those lineages co‐circulated at least during 2013 epidemics. Data from Andrade et al [] suggests the co‐circulation of distinct lineages in other part of Minas Gerais state. In addition, analysis based on envelope sequences obtained from isolates of Rio de Janeiro (in 2010) and Pernambuco (in 2010) also indicated the co‐circulation of lineages BR3 and BR5 in these years in Southeast, Northeast regions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…17 Concurrent circulation of all four serotypes has also been reported in South America and Asia. [29][30][31][32] We provide evidence for the co-circulation of three serotypes. Dengue virus-4 was not detected, although nationwide surveillance data collected in 2000-2011 revealed that DENV-4 is the least common serotype in Mexico.…”
Section: Discussionmentioning
confidence: 74%